EFFETIVENESS OF IMPLEMENTING E-VOTING AS A REPRESENTATION OF ELECTION LAW DEVELOPMENT IN INDONESIA: EFEKTIVITAS PENERAPAN E-VOTING SEBAGAI REPRESENTASI PEMBANGUNAN HUKUM PEMILU DI INONESIA - Muhammad Alief Farezi Efendi (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2023)
This study aims to understand how effective the implementation of e-voting in the election system in Indonesia by analyzing based on the statue approach and a conceptual approach. By using this approach, it can be concluded that if you look at it in terms of needs, it is undeniable that the Indonesian nation is currently in the midst of the current of modernization, it really needs a more up-to-date system with various conveniences and practicalities in its fulfillment. Of course, the application of e-voting must be designed in such a way that elections can be held optimally. In the context of democracy, the voting system through the e-voting method must prioritize, respect, and guarantee the credibility of the election. The development of democratic places in media and the development of technology with a fast flow is one of the strong reasons for the idea of an e-voting system in the implementation of elections in Indonesia. Thus, it is necessary to conduct normative and conceptual studies to be able to build issues and ideas and answers related to the effect of e-voting in the election system in Indonesia as a form and process of building election law in Indonesia, but still in accordance with the principles of holding elections and the provisions of laws and regulations.